Dynamics of Interpersonal Communication in Divorce Mediation: A Case Study of Mediators in Indonesian Religious Courts - Dewi, Novriana; Pragawati; Nofica Andriyati (UIN Sulthan Thaha Saifuddin Jambi, 2025)
Divorce in Indonesia, including in Muaro Jambi Regency, continues to show a high rate and produces significant social consequences. Mediation in religious courts serves as a critical instrument to de-escalate conflict and search for mutually beneficial solutions. This study aims to analyze the dynamics of interpersonal communication used by mediators during divorce mediation at the Sengeti Religious Court. Employing a qualitative case study approach, data were gathered through in-depth interviews with certified mediators, mediation judges, and couples undergoing mediation; non-participant observation; and document analysis of divorce cases from 2023–2024. Data were examined using thematic analysis integrated with Miles and Huberman’s interactive model. Findings reveal that mediators’ interpersonal communication—characterized by empathy, clarity, and participation—plays a pivotal role in mediation success, reflected in a 74.4% settlement rate. Communication strategies such as privacy management through caucus sessions and persuasive approaches based on empathy helped couples shift orientation from conflict toward shared benefits. These findings reinforce the relevance of Social Exchange Theory and Communication Privacy Management Theory in divorce mediation and provide a conceptual contribution to international literature by highlighting mediation practices within the framework of Islamic family law.